2003
DOI: 10.1016/s0896-6273(03)00668-8
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Tetramerization Is Mediated by Q/R Editing

Abstract: AMPA-type glutamate receptors (AMPARs) play a major role in excitatory synaptic transmission and plasticity. Channel properties are largely dictated by their composition of the four subunits, GluR1-4 (or A-D). Here we show that AMPAR assembly and subunit stoichiometry are determined by RNA editing in the pore loop. We demonstrate that editing at the GluR2 Q/R site regulates AMPAR assembly at the step of tetramerization. Specifically, edited R subunits are largely unassembled and ER retained, whereas unedited Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
283
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(311 citation statements)
references
References 51 publications
26
283
2
Order By: Relevance
“…A few sitesincluding the Lurcher site (alanine to threonine mutation) (11,33), the R-Q RNA editing site (43), the flop-flip domains (44), and transmembrane domains (45)-have been suggested to affect the tetramerization step of the assembly, probably by changing the velocity of the second dimerization. Here, we clearly demonstrated that the GluA1 SP plays a critical role in determining the spatial arrangement of heteromeric receptor tetramerization.…”
Section: Discussionmentioning
confidence: 99%
“…A few sitesincluding the Lurcher site (alanine to threonine mutation) (11,33), the R-Q RNA editing site (43), the flop-flip domains (44), and transmembrane domains (45)-have been suggested to affect the tetramerization step of the assembly, probably by changing the velocity of the second dimerization. Here, we clearly demonstrated that the GluA1 SP plays a critical role in determining the spatial arrangement of heteromeric receptor tetramerization.…”
Section: Discussionmentioning
confidence: 99%
“…2d). Although a substantial fraction of GluR2 harbors high-mannose glycans (26,27), GluR2 did not bind Fbx2 (Fig. 2 c and e).…”
Section: Identification Of Fbx2 As a Nr1-ntd-binding Partnermentioning
confidence: 93%
“…AMPARs containing both GluA1 and GluA2 follow GluA1 trafficking rules and override the ER retention of GluA2. Thus, GluA1/2 heteromers rapidly traffic from the ER to the surface whereas AMPARs without GluA1 or GluA4 transit much more slowly 77,78 (Fig. 3).…”
Section: Rna Editing Ampar Assembly and Er Exitmentioning
confidence: 98%